Light emitting composite beams during matrix cracking. (December 2017) - Joshi, Kunal; Mishra, Spandan; Campbell, Chris; Dickens, Tarik; Vanli, Arda
Defects in fiber-reinforced composite structures tend to initiate unpredictably and unalarmed due to local stress concentrations within a composite structure; this has given rise to active monitoring techniques that can quantify the mechanical stress within composites in order to evaluate the structural health. In this paper, triboluminescent mechanisms are used for damage monitoring of composite matrix under flexural loading. Vinyl ester resin is doped with ZnS:Mn phosphors and reinforced with glass fiber whiskers, were subjected to flexural loading while observing both the triboluminescent and acoustic response using a photo multiplier tube (PMT) and micro-mic respectively. Validity of triboluminescent emissions for determining structural integrity of glass fiber / vinyl ester resin composites through individual waveform analysis was examined. Understanding the failure modes through the captured waveform and observed triboluminescent emissions shows that the matrix cracking failure mode tends to lie in the natural frequency range of 2691–2813 Hz. High correlation between the triboluminescent and acoustic signals at matrix cracking at a frequency of 2800 Hz were found. Future research will discuss the triboluminescent and acoustic emissions behavior for delamination and fiber breakage failure modes.